The transformation of traditional Chinese painting in the digital art wave: the impact of AIGC and virtual reality - Cao, Hui (Frontiers in Virtual Reality, 2026)
With the development of computer technology, the digitization of traditional painting has accelerated. Artificial intelligence–generated content (AIGC) and virtual reality (VR) are reshaping the production, dissemination, and aesthetic experience of traditional art, yet a systematic understanding of how they interact with core artistic principles—such as brush–ink logic, spatial conception, and aesthetic intentionality—remains limited. Adopting a systematic and thematic review approach, this paper examines: (1) the technological, aesthetic, and cultural dimensions of digital transformation, showing how digital change extends beyond medium substitution to shifts in viewing logic and meaning construction; (2) how AIGC advances brushstroke simulation, style transfer, and artistic conception but continues to struggle with deeper principles such as spiritual vitality and intention-before-brush; and (3) how VR reconstructs spatial logic and viewing modes in classical painting, revealing tensions between embodied immersion and traditional contemplative, multi-perspective viewing. Drawing on 32 representative studies, this review synthesizes developments in GAN- and diffusion-based generative models as well as VR-based reconstruction and exhibition methods. While AIGC and VR broaden participation by enabling technically trained researchers to engage with traditional culture, the literature also indicates a persistent risk of reproducing surface stylistic features while overlooking essential cultural and spiritual connotations. The paper concludes by identifying key conceptual gaps and proposing future research directions, including mechanism-level modeling of brush-and-ink aesthetics, VR presentation strategies aligned with scattered perspective, and culturally grounded frameworks for human–machine co-creation.